Two Cases of Chronic Forearm Arthritis Caused by Mycobacterium Tuberculosis (International Journal of Food and Nutritional Sciences, 2022)
In the absence of active pulmonary disease, tuberculosis is typically excluded from the differential diagnosis of chronic joint inflammation. The cases of two immigrant patients with forearm tuberculous arthritis are described. In both instances, nonspecific arthritis or trauma was suspected, resulting in a delay of 21 and 24 months, respectively, between the beginning of symptoms and the initiation of specific therapy.Synovial biopsy material was examined histologically and microbiologically to determine the diagnosis. One patient's Mycobacterium tuberculosis complex polymerase chain reaction was positive. The treatment included chemotherapy against tuberculosis, surgical synovectomy, and debridement of the afflicted joints. Although rare, these cases serve as a warning that tuberculosis can induce persistent arthritis.